Exosomes from human placenta purified by affinity chromatography on sepharose bearing immobilized antibodies against CD81 tetraspanin contain many peptides and small proteins. Issue 11 (2nd October 2018) - Burkova, Evgeniya E.; Dmitrenok, Pavel S.; Bulgakov, Dmitrii V.; Vlassov, Valentin V.; Ryabchikova, Elena I.; Nevinsky, Georgy A.
Abstract: Exosomes are nanovesicles (40–100 nm) containing various RNAs and different proteins. Exosomes are involved in intracellular communication and immune system function. Exosomes from different sources are usually isolated using standard methods—centrifugation and ultracentrifugations. Exosomes isolated by these procedures were reported to contain from a few dozen to thousands of different proteins. Here crude vesicle preparations from five placentas (normal pregnancy) were first obtained using standard centrifugation procedures. According to electron‐microscopic studies, these preparations contained vesicles of different size (30–225 nm), particles of round shape of average electron density ("nonvesicles" 20–40 nm) (A), structured clusters of associated proteins and shapeless aggregations (B), as well as ring‐shaped 10–14 nm structures formed by ferritin (C). After additional purification of the vesicle preparations by gel filtration on Sepharose 4B, the main part of protein structures was removed; however, the preparations still contained small admixtures of components A–C. Further purification of the preparations by affinity chromatography on Sepharose bearing immobilized antibodies against exosome surface protein CD81 led to isolation of highly purified exosomes (40–100 nm). These exosomes according to electron microscopy data contained tetraspanin embedded in the membrane, which was stained with antibodies against CD81 conjugated with 10–12 nm gold nanoparticles. SDS‐PAGE and MALDI MS and MS/MS mass spectrometry of tryptic hydrolysates of proteins contained in these exosomes revealed eleven major proteins (>10 kDa): hemoglobin subunits, CD81, interleukin‐1 receptor, annexin A5, cytoplasmic actin, alpha‐actin‐4, alkaline phosphatase, human serum albumin, serotransferrin, and lactotrasferrin. Using MALDI mass analysis of the highly purified exosomes, we for the first time found that in addition to the large proteins (>10 kDa), exosomes having affinity to CD81 contain more than 27 different peptides and small proteins of 2–10 kDa. This finding can be useful for revealing biological functions of pure exosomes. © 2018 IUBMB Life, 70(11):1144–1155, 2018